PENINGKATKAN PEMBELAJARAN TOLAK PELURU MELALUI PENDEKATAN SUDUT ELEVASI PADA SISWA KELAS V SDN KALIREJO 02 KAB. BATANG TAHUN PELAJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The results of this study are: Conclusions are based on data from the research results, the first cycle and secondcycle using Standard Reference Rate or KKM set by the school as a reference value of 70 completed the study.From the results of the implementation cycle I have improved but have not been up to that desired by theresearcher, the continued improvement of the learning cycle II results obtained over the maximum it canterliahat on the implementation of instructional improvement cycle I was only 6 students (64%) have notcompleted the learning , while in the second cycle of 15 students have completed their study (88%).Increasing the quality of the learning process would logically lead to greater student achievement, theconclusion of the research conducted is that the use of the elevation angle approaches proven to improve theeffectiveness of learning in the shot put Elementary School fifth grade students Kalirejo 02..